Covid-19 Therapy: What Have We Learned In 8 Months? - Adamczyk-Popławska Monika; Kwiatek Agnieszka (Postępy Mikrobiologii, 2020)
SARS-CoV-2, a novel pathogenic human coronavirus, emerged in December of 2019 in Wuhan (Hubei province, China). In most cases, the infection causes a mild to moderate respiratory illness. However, a undefined group of infected may develop a severe or critical illness: Coronavirus disease 2019 (COVID-19) with acute respiratory distress syndrome (ARDS) and many other complications. Current efforts are focused on limiting the spread of the virus in the population. COVID-19 treatments are intensively evaluated, however, 8 months since the start of the pandemic and despite hundreds of clinical trials, our knowledge of effective treatments is still poor. In this review, we present the current status of drugs and treatments used during SARS-CoV-2 infection. Host-directed and virus-directed drugs, as well as new compounds specific for SARS-CoV-2 are presented.